The spectres of Andrés Bello in the Chilean academy - Durán del Fierro , Francisco (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2024)
In Chile, the contemporary form of academic life is irreducible to neoliberalism. There are pastexperiences and discourses that continue to disrupt the daily routine, dynamics, intensity, andrhythm of academics. They manifest as various epistemological, ethical, institutional, technical, andpolitical mechanisms that produce innumerable images, meanings, and practices. Theseexperiences conflict with the affects and material realities of the neoliberalism. The entanglementof these experiences from the past and present is conflicting, as they attempt to ignore or represseach other. In this respect, this paper addresses the following question: what is the model ofacademic behaviour that was established during the post-independence period in the Chileanuniversity system? To answer this question, I explore Andres Bello's texts concerning university andacademic life. The conclusion is that Bello established a specific model of academic behaviour that,with some later modifications, reconfigurations, and contradictions, returns to the present. Bello'sinfluence today can be seen through spectres that enable and limit new possibilities for expandingacademic critique within and across scholarly settings.